2016
DOI: 10.1187/cbe.15-03-0062
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Use of Student-Centered Pedagogies from Moderate to High Improves Student Learning and Attitudes about Biology

Abstract: Students in an extensively student-centered biology class using multiple active-learning pedagogies and consistent formative assessment had greater content gains and more sophisticated views about learning biology compared with students in a moderately student-centered section using fewer active-learning pedagogies and less formative assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 68 publications
3
96
1
Order By: Relevance
“…We targeted student perceptions of active-learning experiences, establishing buy-in as a viable explanation for the consistent link between active learning and enhanced learning outcomes in the sciences established elsewhere (Armbruster et al ., 2009; Freeman et al ., 2014; Connell et al ., 2016). Our findings revealed that students who reported more substantial buy-in to active learning were more likely to engage in the types of self-regulated learning behaviors that often lead to academic success.…”
Section: Discussionmentioning
confidence: 99%
“…We targeted student perceptions of active-learning experiences, establishing buy-in as a viable explanation for the consistent link between active learning and enhanced learning outcomes in the sciences established elsewhere (Armbruster et al ., 2009; Freeman et al ., 2014; Connell et al ., 2016). Our findings revealed that students who reported more substantial buy-in to active learning were more likely to engage in the types of self-regulated learning behaviors that often lead to academic success.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, by reinforcing perceptions of students' positive autonomy-related traits through targeted workshops, one can improve both student selfconfidence and autonomous learning traits (Macaskill and Denovan 2013). These studies and recent student surveys suggest that many key traits that underlie autonomy may be developed by independent, student-led learning practices (NSSE 2016;Connell et al 2016).…”
Section: Introductionmentioning
confidence: 96%
“…There is a abundant literature supporting the notion that providing students with opportunities to engage in the process and practice of science enhances their learning experiences (Russell et al ., 2007; Freeman et al ., 2014; Wieman, 2014; Connell et al , 2016). It is not only essential to provide engaging opportunities for students, but also important to assess whether or not those opportunities are indeed enhancing student learning (Momsen et al , 2013; Freeman et al ., 2014; Wieman, 2014; Brame and Biel, 2015; Couch et al ., 2015).…”
Section: Methods and Resultsmentioning
confidence: 99%